Disturbance rejection for singular Markovian jump systems with time-varying delay and nonlinear uncertainties. (August 2019) - Mohanapriya, S.; Sakthivel, R.; Kwon, O.M.; Marshal Anthoni, S.
Abstract: This paper employs an active disturbance rejection technique for a class of singular Markovian jump systems with external disturbances, time-varying delay and unknown nonlinear uncertainty. Based on the improved equivalent-input-disturbance approach, a robust modified repetitive controller is proposed to the considered system to solve the periodic output tracking problem. An appropriate Lyapunov–Krasovskii functional is selected to guarantee the mean-square asymptotic admissibility of the system under study. Moreover, an explicit expression of the proposed controller is presented which has the capability of forcing the system output to exactly track any given periodic reference signal. Finally, the obtained results are validated through simulations by considering a DC motor driving model to demonstrate the effectiveness of the proposed control design technique.